Multifractal characterization of unworn hydrogel contact lens surfaces. Issue 5 (5th July 2013) - Ţălu, Ştefan; Stach, Sebastian
<x xml:space="preserve">Abstract</x> Purpose: The aim of this work was to estimate the multifractal spectra of 3D surface roughness for unworn hydrogel contact lenses (CL), obtained with atomic force microscopy (AFM) analysis. Materials and methods: Contact lenses made from vifilcon A (Focus® Monthly Toric Visitint® model, CIBA Vision Corp.) were investigated. CL surface roughness was studied by AFM in tapping‐mode™, in an aqueous environment, on square areas ranging from 1 to 4 μm2. A detailed methodology for CL surface multifractal characterization, which may be applied for AFM data, was presented. Results: The CL surface roughness revealed multifractal geometry at various magnifications. The generalized dimension Dq and the singularity spectrum f(α) provided quantitative values that characterize the local scale properties of CL surface geometry at nanometer scale. Conclusions: Multifractal analysis provides different yet complementary information to that offered by traditional surface statistical parameters. POLYM. ENG. SCI., 54:1066–1080, 2014. © 2013 Society of Plastics Engineers